Sacral Architecture of Czestochowa—The “Spiritual Capital of Poland” over the Centuries and Nowadays - Aleksandra Repelewicz; Zaruhi Mamyan (Religions)
Częstochowa is a city known as the “spiritual capital of Poland”. The reason behind this name is the sanctuary of Our Lady—”Jasna Góra” monastery—around which a settlement was established, giving rise to the city today. The first parish was established in the 14th century. The next two parishes in Częstochowa were only established at the turn of the 19th and 20th centuries: St Barbara’s in 1891 and St Joseph’s in 1910. Today, Częstochowa has a population of almost 200,000, is an industrial and academic center, and has 53 parish churches. In comparison, Warsaw, Poland’s capital, with a population of 1,861,599, has 86 parishes. The vast majority of Częstochowa’s churches were built in the 1980s and 1990s. This paper presents a short history of the city’s development with particular reference to its sacred architecture. It also attempts to present the influence of church buildings on the urban layout and religious atmosphere of the city. The paper is an attempt to present the phenomenon of Częstochowa, which attracts hundreds of thousands of pilgrims from Poland and all over the world every year.